2022
DOI: 10.1177/08839115221095152
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of miRNA-126 through folic acid-targeted biocompatible polymeric nanoparticles for effective lung cancer therapy

Abstract: Objective: Nanoparticle-based drug delivery systems (DDSs) have been playing a considerable role in the eradication of cancer. In this experimental study, we designed and synthesized folic acid (FA)-decorated chitosan (CS) nanocarrier for targeted delivery of miR-126 (as a therapeutic agent) to lung cancer A549 cells. Materials and methods: Therefore, the FA-CS-miR-126 nano-complex was perfectly developed and characterized by various analytical devices such as Fourier transform infrared (FT-IR) and dynamic lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Polyethyleneimine (PEI), the most common type of polyplexes, was used to deliver miR-33a and miR-145 to colon carcinoma tissues in a mouse model, resulting in tumor proliferation reduction and cell apoptosis increase [ 270 ]. Another study used a three-layered polyplex of a PEI core, a polyethylene glycol (PEG) intermediate layer, and a folic acid-modified chitosan outer layer to systemically deliver miRNA-126 into lung cancer cells [ 271 ]. The results showed that this polyplex could efficiently deliver miRNA-126 and inhibit tumor growth in vivo [ 271 ].…”
Section: Delivery Tools For Mirna Therapeutic Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyethyleneimine (PEI), the most common type of polyplexes, was used to deliver miR-33a and miR-145 to colon carcinoma tissues in a mouse model, resulting in tumor proliferation reduction and cell apoptosis increase [ 270 ]. Another study used a three-layered polyplex of a PEI core, a polyethylene glycol (PEG) intermediate layer, and a folic acid-modified chitosan outer layer to systemically deliver miRNA-126 into lung cancer cells [ 271 ]. The results showed that this polyplex could efficiently deliver miRNA-126 and inhibit tumor growth in vivo [ 271 ].…”
Section: Delivery Tools For Mirna Therapeutic Approachesmentioning
confidence: 99%
“…Another study used a three-layered polyplex of a PEI core, a polyethylene glycol (PEG) intermediate layer, and a folic acid-modified chitosan outer layer to systemically deliver miRNA-126 into lung cancer cells [ 271 ]. The results showed that this polyplex could efficiently deliver miRNA-126 and inhibit tumor growth in vivo [ 271 ]. PLGA NPs could increase their miRNA encapsulation efficiency by preparing with positively charged molecules like PEI or chitosan [ 272 , 273 ].…”
Section: Delivery Tools For Mirna Therapeutic Approachesmentioning
confidence: 99%
“…Many researchers have reported certain reactions to introduce extra hydrophilic or hydrophobic groups onto the chitosan macromolecules, depending on the application. Several ligands have been utilized, such as glutathione [ 80 ], galactose [ 75 , 81 ], mannose [ 82 ], aptamers [ 83 , 84 ], folic acid [ 85 , 86 ], RGD [ 87 ], and REDV peptides [ 88 , 89 , 90 ], to chemically modify the side groups of chitosan for specific cell targeting. The PEGylation of chitosan is a common strategy utilized for the increase in hydrophilicity, stability, and bioavailability, the avoidance of opsonization, and the reduction in toxicity [ 91 , 92 ].…”
Section: Chitosan Complexes For Nucleic Acid Deliverymentioning
confidence: 99%
“…Moreover, surface functionalization of chitosan NPs became a valid option to investigate active targeting ensuring better uptake and higher transfection efficiency. Ligands such as REDV peptide in the works of Zhou et al [39,54,55], RGD peptide [56], aptamers [33,57], folic acid [58,59], galactose [24,60], mannose [61], and glutathione [50] have all been investigated within the scope of CS/miR NPs. Most studies were concerning active targeting against cancer cells, however, Pereira et al investigated the use of lactoferrin and stearic acid to enhance the brain targeting ability of their CS nanoplexes to treat Alzheimer's disease [62].…”
Section: Chemical Modifications To Chitosan Reported In Mirna Formula...mentioning
confidence: 99%